Evaluation of antifungal molecules against Alternaria helianthi causing leaf blight in sunflower: Evaluation of antifungal molecules against Alternaria helianthi causing leaf blight in sunflower - K KARUNA; C P MANJULA; ABHILASH (Journal of Oilseeds Research, 2020)
In sunflower the yield loss reported due to the major destructive disease, Alternaria leaf blight varies from 11.30 to 73.33 per cent. Among the nano particles and fungicides evaluated against Alternaria helianthi, Azoxystrobin (98.49) in systemic fungicides, Propiconazole + Difenoconazole (91.29) in combi products and silver colloidal particles (52.72) in nano particles were efficient ones in inhibiting the pathogen under in vitro assay.